SOSIALISASI PENTINGNYA PENDIDIKAN INOVASI TEKNOLOGI PEMBELAJARAN - Hetwi Marselina Saerang; Harol R. Lumapow; Viktory Nicodemus Joufree Rotty (Jurnal Abdimas Bina Bangsa, 2023)
Changes in the use of technology are taking place in the world of education. There are three main changes currently taking place, namely (1), the emergence of extensive (broad) use of technology, (2), the transition to the use of technology from elementary schools to high schools, (3), the introduction of a national curriculum using the Information Communication system and Technologies” (ICT). Innovation can be thought of as having a cycle with four phases: (1), idea generation and invention; (2), idea selection; (3), implementation of ideas; and (4), the diffusion of ideas (Eggers & Singh, 2019). Innovation offers benefits and can include the introduction of knowledge. Hence how do people see the word 'innovation' in education, as Norton (2013:1) argues that “more innovation needs to be encouraged in education so that students can benefit from new technologies through face-to-face and online approaches; or Innovation High School (2012: 1) states that "they provide technology in the learning environment for all students by adjusting education to suit the individual needs of the students themselves. Innovation means many new things, and creative for the development of education, so that the old way is no longer effective. The 2022 national curriculum uses the Information Communication and Technologies (ICT) system for all subjects. The use of technology in mathematics began with scientific calculators and is now being extended to graphical calculators and computer programs. Image and sound recording facilities are enhanced through the submission of assignments. The presence of technology creates its own worries for teachers, students who are not ready to accept change and individualistic attitudes emerge. The common issues discussed here regarding teacher anxiety and the use of technology are currently taking place in schools. Problem solving for students generally requires a type of pedagogy that is often adapted to the needs of individual students. This requires far more innovative practices than before because a large number of students still exhibit apprehension about using learning technology. Therefore, it takes innovation and creativity to overcome the problem of learning to use technology.